Pengaruh Keterampilan, Kreativitas, dan Motivasi Terhadap Kualitas Pembelajaran Siswa SMP - Mulyana M; Nisma Iriani; Baso Amang; Asikin Muchtar; Wahyudi Putera (TIN: Terapan Informatika Nusantara, 2023)
The approach in this study is an associative approach, an associative approach is an approach where to find out that there is a relationship or influence between the two variables (independent variable and dependent variable). In this study, the independent variable X1 is teaching skills, X2 is teacher creativity, X3 is teacher motivation and the dependent variable Y is learning quality. The data analysis technique starts from collecting information through a questionnaire in the form of questions and statements and at the final stage by drawing conclusions. Based on the results of the study, it can be concluded that the partial test of teaching skills has a positive and significant effect on the quality of learning of students of public junior high school 33 Makassar City. Furthermore, teacher creativity has a positive and significant effect on the quality of student learning in public junior high school 33 Makassar City. Then also teacher motivation has a positive and significant effect on the quality of student learning in public junior high school 33 Makassar City. After testing simultaneously together and found that teaching skills, teacher creativity and teacher motivation have a positive and significant effect on the quality of learning of students of public junior high school 33 Makassar City.